Purification and Characterization of Alginate Lyase from Mucoid Pseudomonas aeruginosa Strain 214 - Hoda Gol Fakhrabadi; Parinaz Ghadam; Parisa Mohammadi; Ahya Adbi Ali (Journal of Genetic Resources, 2015)
Pseudomonas aeruginosa is an opportunistic pathogen that causes a variety of infections in compromised patients. The ability of Pseudomonas aeruginosa to produce chronic infection is based in part on its ability to biosynthesis of biofilm, and alginate is the major polysaccharide in the synthesized biofilm. So alginate degradation is very essential in the dispersion of Pseudomonas aeruginosa biofilm. Alginate lyase is an important enzyme in alginate degradation. This enzyme is different, especially with respect to molecular weight, pI and substrate specificity in various bacteria and even in various strains of a bacterium. The amount of alginate in mucoid strains is more than in nonmucoid strains. In this study, P. aeruginosa strain 214 was selected because it forms highly mucoidal colonies and thus it is a good candidate for alginate lyase preparation. Alginate lyase was extracted from the periplasmic space of P. aeruginosa by the use of heat shock method. Thiobarbitoric acid assay was used for measuring the activity of alginate lyase. This enzyme showed the most activity in Tryptic Soy Broth (TSB) medium. The optimum concentration of sodium alginate was 0.02 mg/ml and the optimum activity of the enzyme was found in 20 min reaction time at 37°C. The enzyme was purified by a simple two-step procedure; ammonium sulfate precipitation and ion exchange column chromatography DEAE-Sepharose Cl-6B. Sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) suggested a molecular weight of approximately 40 kDa for alginate lyase.